2014
DOI: 10.3399/bjgp14x682825
|View full text |Cite
|
Sign up to set email alerts
|

Relationship continuity: when and why do primary care patients think it is safer?

Abstract: BackgroundDoctor-patient continuity is popular with patients and practitioners, and is associated with better outcomes; however, changes in policy and practice organisation have diminished its scope. Although there has been some discussion of safety implications from professionals' perspective, patients' views remain largely unexplored. AimTo explore patients' understanding of safety in primary care. Design and settingAn interview-based study with patients from general practices in the northwest of England. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 8 publications
2
56
0
Order By: Relevance
“…A central clinical implication is therefore to preserve these continuous professional-patient relationships, with potential implications for psychological patient safety. [43] Our findings suggest professionals to have well-defined roles in which they feel confident and competent, suggesting additional training to broaden their remit would not be perceived as feasible. More integrated models of care, with joint working between primary care, specialist MS services and mental health services may help ensure appropriate access to services and support for both patients and professionals.…”
Section: Implications For Clinical Practicementioning
confidence: 75%
“…A central clinical implication is therefore to preserve these continuous professional-patient relationships, with potential implications for psychological patient safety. [43] Our findings suggest professionals to have well-defined roles in which they feel confident and competent, suggesting additional training to broaden their remit would not be perceived as feasible. More integrated models of care, with joint working between primary care, specialist MS services and mental health services may help ensure appropriate access to services and support for both patients and professionals.…”
Section: Implications For Clinical Practicementioning
confidence: 75%
“…Obviously I never saw him again. (F.31) Seeking continuity with a familiar and trusted GP was also a common strategy which is reported in detail elsewhere (Rhodes et al 2014). For example, one respondent talked about the difficulties of managing to get an appointment with a doctor who they had already con-sulted with, and with whom they wanted a further consultation.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on continuity of care, however, were carried out in countries in which the choice is subject to stricter rules and is more restrictive. 4,5,17,18 Previously, it has been reported that trust encourages loyalty. [13][14] In the present study, this appeared essential to creating and maintaining loyalty.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The topics addressed were chosen based on data from the literature and test interviews. 2,[4][5][6]9,[13][14][15] About 15 topics were selected (Boxes 1 and 2).Interviews were conducted between March and July 2015 and the interviews were carried out until data sufficiency was confirmed.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation